A Review of Ética y seguridad en la investigación. Aprendizajes y desafíos - Velásquez Díaz, Laura María (Revista de Psicología, 2023)
Editors: Alejandra Santana López and Luca Valera Publisher: Ediciones UC Place of publication: Santiago, Chile Year: 2022 Number of pages: 442 ISBN number 978-956-14-3051-1 Digital ISBN: 978-956-14-3051-8 Editors’ data: Alejandra Santana López is a social worker, Master’s in Psychology and Education, and PhD in Educational Sciences from the P. Universidad Católica de Chile. She graduated in Research Ethics with human beings (Universidad de Chile). She is coordinator of the UC Research Ethics and Safety Unit. She is the author of the book Investigación formativa. Herramientas para la educación superior (2022). Luca Valera studied Philosophy at the Università Cattolica del Sacro Cuore di Milano and is a doctor in Bio-ethics from the Università Campus Bio-Medico di Roma. He is a professor at the P. Universidad Católica de Chile. He is the author of various books, including Espejo. Filosofía y nuevas tecnologías (2022). He is editor of the Manual de ética aplicada: de la teoría a la práctica (UC Editions, 2021). He was director and is currently a member of the UC Bioethics Centre and is a Visiting Professor in the Department of Philosophy at the Universidad de Valladolid (Spain).